Medication adherence in a nurse practitioner managed clinic for indigent patients. Issue 8 (13th February 2015) - Alton, Suzanne; March, Alice L.; Mallary, Laura; Fiandt, Kathryn
Abstract Purpose Little is published in the literature about medication adherence rates among patients who are medically indigent and patients receiving primary care from nurse practitioners (NPs). This project examined adherence rates and barriers to adherence among patients at an NP‐managed health clinic (NPMC). Data sources The setting for this research was an NPMC for uninsured and low‐income patients. A cross‐sectional convenience sample of patients (n = 119) completed surveys eliciting demographic information, self‐report of medication adherence, health literacy, and barriers to adherence. Conclusions Analysis of subjects demonstrated a vulnerable population, yet the mean adherence rate was surprisingly high (77%), compared to the rate usually cited in published literature. The best predictive model differentiating patients with high adherence from those with low adherence combined the total number of reported barriers, health literacy, and employment status. The barriers most frequently cited by subjects were difficulty paying for medications, and difficulty reading and understanding written prescription labels, which was particularly prevalent among Spanish‐speaking patients. Implications for practice Clinic efforts to improve patient access to affordable medications may have contributed to subjects' high rates of adherence. These efforts included helping patients with filling out prescription assistance program paperwork, prescribing generic medications, providing samples, and providing effective patient education.